Tilapia: From the Nile to the world. - Abdelhadi, Yasser Mohamed (2011)
This study addressed the potential of tilapia aquaculture as a major contributor to food production and poverty alleviation all over the world. To encompass this subject, tilapia history, origin, aquaculture potential, constraints, current and future production levels were reviewed. Tilapias are native to the River Nile and Africa in general then they were introduced and disseminated worldwide. Positive aquacultural characteristics of tilapia made tilapias the most cultured species worldwide now and in the near future. Tilapia world production is expected to reach 3 million tons this year 2010. Thus, tilapias could make a significant contribution to the livelihoods support especially in the tropical and subtropical countries.